Increasing Coastal Disaster Resilience Using Smart City Frameworks: Current State, Challenges, and Opportunities - Tonmoy, Fahim Nawroz; Hasan, Samiul; Tomlinson, Rodger (Frontiers in Water, 2020)
Sea-level rise, storm surges and floods in coastal cities have already threatened large population and infrastructure with potential to increase significantly in future as climate changes. Therefore, increasing coastal disaster resilience has become a major priority for coastal cities. At the same time, recent development in information technology, ubiquitous sensors, advanced data science allow us to generate insights that were unimaginable before and can assist in better managing coastal disaster risks. In this paper, using an infrastructure resilience lens, we critically review a set of academic literature that focus on the new development of smart systems in coastal disaster management and a set of use cases that focus on their practical application in different coastal cities. We find that smart city technologies such as internet of things (IoT) and crisis informatics have significant potential and have been increasingly used in academic studies but their city scale applications in coastal disaster management have been limited. We then discuss challenges and opportunities of using smart city frameworks for increasing disaster resilience of coastal communities.